PENINGKATAN KEMAMPUAN PERBENDAHARAAN KATA MELALUI PERMAINAN BONEKA TANGAN - Sitti Hatika; Syamsul Alam Ramli (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2022)
Low Vocabulary Ability of Children in Group A Kindergarten Tunas Bangsa, Sukamaju District, North Luwu Regency. Action research cycle refers to Mc Kernan's action research model which divides into 7 stages, namely situation analysis (reconnaissance), problem formulation and clarification, action hypothesis, action planning, implementation of action with monitoring, evaluation of action results, reflection and decision making for further development . Overall, the average vocabulary ability through hand puppets increased from an average of 8.12 or 34% in cycle 1 to 19.24 or 80% in cycle 2 with an average increase of 11.12 or 46%, thus the success rate of children's abilities based on Mills' action success criteria ≥71% vocabulary ability through hand puppets in group A TK Tunas Bangsa, Sukamaju District, North Luwu Regency was found to have experienced success.